Peran Guru Kelas Dalam Meningkatkan Motivasi Belajar Di Era Digital - Subhan Adi Santoso (Jurnal Pendidikan Bahasa Arab, 2025)
Classroom teachers are key elements in the educational process, especially at the elementary school level. Classroom teachers not only serve as conveyors of material, but also as mentors, classroom managers, learning facilitators, and role models for students. These complex roles and responsibilities have been discussed in various educational theories. This study aims to describe the main theories regarding classroom teachers, including teacher role theory, competency theory, classroom management theory, pedagogy theory, constructivism theory, and classroom teacher task theory. This research was conducted at Muhammadiyah Elementary School in Gresik, because according to the title of the research, Muhammadiyah Elementary School in Gresik is one of the institutions that has successfully implemented digital technology, enabling Muhammadiyah Elementary School in Gresik to develop rapidly in a short period of time. The results of the study show that teachers can act as facilitators, motivators, digital classroom managers, innovators, and digital literacy mentors. Digital technology can be a very effective tool for increasing student motivation if used appropriately and creatively. Guru kelas merupakan elemen kunci dalam proses pendidikan, terutama pada jenjang sekolah dasar. Guru kelas tidak hanya berperan sebagai penyampai materi, tetapi juga sebagai pembimbing, pengelola kelas, fasilitator pembelajaran, dan teladan bagi peserta didik. Peran dan tanggung jawab yang kompleks ini telah dibahas dalam berbagai teori pendidikan. Penelitian ini bertujuan menguraikan teori-teori utama mengenai guru kelas, meliputi teori peran guru, teori kompetensi, teori manajemen kelas, teori pedagogi, teori konstruktivisme, serta teori tugas guru kelas. Penelitian ini dilakukan di Sekolah Dasar Muhammadiyah Gresik, karena sesuai dengan judul yang diteliti di Sekolah Dasar Muhammadiyah Gresik merupakan salah satu lembaga yang telah berhasil memfungsikan digital dengan baik sehingga dalam waktu singkat Sekolah Dasar Muhammadiyah Gresik bisa berkembang dengan sangat pesat. Hasil penelitian sebagai fasilitator, motivator, pengelola kelas digital, inovator, dan pembimbing literasi digital. Teknologi digital dapat menjadi alat yang sangat efektif untuk meningkatkan motivasi siswa jika digunakan dengan tepat dan kreatif.